Electrically conductive organic polymers for advanced applications - Cotts, David B. (Noyes Data Corp., 1986)
Surveys the properties of electrically conducting, semiconducting, and semi-insulating polymers; evaluates their conduction mechanisms, mechanical properties, and suitability for space-based use and other advanced applications.